Species delimitation and phylogenetic analyses reveal cryptic diversity within Cerebratulus marginatus (Nemertea: Pilidiophora). Issue 7 (3rd October 2021) - Verdes, Aida; Arias, María Belén; Junoy, Juan; Schwartz, Megan L.; Kajihara, Hiroshi
Abstract : The heteronemertean Cerebratulus marginatus Renier, 1804 is a well-known representative of the family Lineidae (Nemertea) inhabiting sandy or muddy sediments throughout the world. Due to its wide geographic distribution and the lack of distinctive external morphological features among different populations, the species has been considered cosmopolitan. Increasing evidence indicates that nemertean species, including Cerebratulus marginatus, described based on morphology are often not supported by genetic data and represent complexes of cryptic species, rather than cosmopolitan species. Here, we use species delimitation and phylogenetic analyses to evaluate the speciation patterns within the putative C. marginatus species complex. We examined 25 specimens morphologically ascribed to C. marginatus and closely related species using a multilocus dataset including two mitochondrial markers ( 16S rRNA, COI ) and three nuclear markers ( 18S rRNA, 28S rRNA, H3 ). Our analyses identified at least four supported independent lineages among the populations analysed, indicating that samples identified as C. marginatus might represent indeed a complex of cryptic species. Therefore, our results do not support the cosmopolitanism of C. marginatus and provide additional evidence suggesting that species identifications in nemerteans should not be based exclusively on morphological or anatomical features which do not accurately reflect evolutionary patterns. Our study highlights the importance of including molecular data in addition to morphological information to accurately delimit species boundaries, thereby improving nemertean taxonomy by providing a more accurate picture of the true species diversity and geographic distribution of this typically neglected phylum.